Regulation of ethylene-responsive SlWRKYs involved in color change during tomato fruit ripening - Wang, Ling (Sci Rep, 2017)
WRKY transcription factors (TFs) play important roles in stress responses in planta. However, the function of WRKY TFs in the regulation of fruit ripening is unclear. Here, 23 tomato SlWRKYs that are similar to ethylene-responsive WRKY genes from other plant species, or show up-regulation during fruit ripening in previous genome-wide study, were selected, and their function in fruit ripening was investigated. Twelve SlWRKYs were found to be responsive to ethylene (SlER-WRKYs), showing expression patterns similar to those of genes related to fruit ripening. Eight SlER-WRKYs—SlWRKY16, 17, 22, 25, 31, 33, 53, and 54, detected in the nuclei—interacted with and activated the promoters of 4 genes related to color change: Pheophytin Pheophorbide Hydrolase (SlPPH), Pheophorbide a Oxygenase (SlPAO), Phytoene Synthase 1 (SlPSY1) and Phytoene Desaturase (SlPDS). Yeast two-hybrid and bimolecular fluorescence complement (BiFC) assays in Arabidopsis protoplasts indicated that protein interactions occurred between SlWRKY17 and SlRIN, SlERF2b or SlERF7; SlWRKY33 and SlERF7; SlWRKY54 and SlERF2b; and SlWRKY16 and SlWRKY17. Suppression of SlWRKY 16, 17, 53 or 54 by virus-induced gene silencing (VIGS) retarded the red coloration of the fruit. Our study provides comprehensive molecular evidence that WRKY TFs function in fruit ripening, particularly in color change, and are linked to the intricate regulatory network of other ripening regulators.